Knowledge, Attitude and Practices of self-medication among medical students of Government Medical College, Baroda, Gujarat - Pathak , Akhilesh K (Journal of Indian Academy of Forensic Medicine, 2020)
Self-medication is a commonly found behaviour world-wide in which the people use drugs to self-administered treatment for their  physical or psychological illness. Self-medication involves obtaining medicines without a prescription, resubmitting old prescriptions  to purchase medicines, sharing medicines with relatives or members of one's social circle or using leftover medicines stored at home.  Self-medication is an essential part of self-care, which is quite common in India due to easy availability of drugs without prescription.  It is considerably high in medical students and paramedics due to their knowledge of medicine. The drugs, which are most frequently  used for self-medication are antibiotics, analgesics, antipyretics, antihistaminics, antitussives, multivitamins, anthelmintics, etc. The  prevalence of self-medication among medical students in Central Gujarat is not known and hence this project was undertaken to assess  the prevalence of self-medication among the undergraduate students of Government Medical College, Baroda and to assess their  knowledge, attitude and practices of self-medication.
Keywords: Self medication; Self care; self-administered treatment